Q. 1 B3.7( 3 Votes )

Check whether the

Answer :

Let us solve the above equation,

(x + 2)3 = x3 – 4


x3 + 3x2 × 2 + 3x × 4 + 8 = x3 – 4


x3 + 6x2 + 12x + 8 = x3 – 4


x3 + 6x2 + 12x + 8 - x3 + 4 = 0


6x2 + 12x + 12 = 0


6(x2 + 2x + 1) = 0


x2 + 2x + 1 = 0


Since on solving the equation we do get the second power of x which proves that the following set of equation is quadratic


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Check whether theRajasthan Board Mathematics

Check whether theRajasthan Board Mathematics

Check whether theRajasthan Board Mathematics

Check whether theRajasthan Board Mathematics